Prognostic value of non-alcoholic fatty liver disease in patients with pulmonary embolism - Kaçmaz Kat, Nurcan; Sensoy, Nur Ozer; Kuzeytemiz, Mustafa; Demir, Ömer Furkan (The European Research Journal, 2024)
Objectives: Pulmonary embolism (PE) is an important disease due to its mortality and morbidity-related clinical conditions. Patients with a high risk of death within 30 days are discriminated against with the help of various clinical scores. Non-alcoholic fatty liver disease (NAFLD) has been found to be associated with atherosclerosis. We aimed to investigate the effect of NAFLD on disease severity and early death rate in patients with pulmonary embolism. Methods: This retrospective study includes patients who applied to the emergency department with suspected pulmonary embolism and whose diagnosis was confirmed according to the results of the examination. In addition to confirming the diagnosis of PE, hepatic steatosis was detected and graded by tomographic examination of the liver and spleen. Disease severity was stratified by Simplified Pulmonary Embolism Severity Index (sPESI). Results: A total of 165 patients (105 with sPESI≥1 and 60 with sPESI<1 controls) were included. The rate of mortality was 12% (n=13) in the sPESI≥1 group. The prevalence of NAFLD was 64% and the prevalence of hepatosteatosis was similar according to disease severity and prognosis (67% vs. 58%; P=0.28 and 69% vs. 63%; P=0.77). Besides the effect of disease severity; chronic lung disease (CLD) and chronic kidney disease (CKD) were independently associated with poor prognosis by multivariate analysis [3.71 (1.02-13.46); P=0.04 and 15.89 (2.57-98.35); P=0.003]. Conclusion: No association between disease severity and prognosis was observed with NAFLD in acute PE disease.